RHEOLOGICAL, THERMOMETRIC AND GEOCHEMICAL SIGNATURES OF OIL AND GAS BEARING CAPACITY OF THE WESTERN KAMCHATKA SHELF - Petrishchevsky, A.M. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2025)
The relations of structural, rheological, thermophysical and geochemical characteristics of the Earth's crust of West Kamchatka with the adjacent shelf are studied. This oil-and-gas-bearing region is confined to the region of juxtaposition of the Pacific crust, pushed under Kamchatka, with the Okhotskplate. The lower layer of the Kamchatka crust with lower density is a source of thermal anomalies that provide optimal conditions for catagenesis of oil (temperature 120–130 °C) and gas (temperature 200–00 °C) deposits in the upper layers of the crust. The temperature characteristics of the upper crust of the West Kamchatka shelf are identical to those of the oil and gas bearing area on the northeastern shelf of Sakhalin Island. On the West Kamchatka shelf, zones of reduced density contrast in the lower crust and thermal anomalies are correlated with geochemical signatures of oil and gas accumulation, as well as with gas deposits in the southwest of the peninsula (in the Kolpakovsky Trough). On the southern flank of the West Kamchatka shelf, signs of a central-type structure were found, which divides the West Kamchatka trough into southern gas-bearing and northern oil-bearing zones. Prospects of future oil and gas prospecting in this area are estimated.